The Nationality Da’wah Method of Habib Luthfi Ali bin Yahya in Indonesia - Surur, Achmad Tubagus; Anas, Ahmad; Riyadi, Agus; Shulthoni , Muhamad; Adinugraha, Hendri Hermawan (Unisia, 2024)
This research aims to reveal the da'wah and broadcasting approaches to seek the principles of Islamic da'wah and examine the da'wah media used by Habib Luthfi Ali bin Yahya. This type of research is qualitative research. Primary data is broadcast recordings of Habib Luthfi Ali bin Yahya. Secondary data, namely several kinds of literature relevant to this research's purpose, is supportive. The data collection technique is documentation. The researcher uses a qualitative descriptive analysis of cultural criticism theory, namely an analysis of the understanding of how a person communicates and how to develop symbolic meaning in society. The results of this study indicate that the role of ulama and religious leaders as missionaries is significant and strategic in preaching. The existence of the figure Habib Luthfi bin Ali Yahya has significantly contributed to the spread of Islamic da'wah. Their love of the motherland missionary movement is quite relevant amid the current condition of the Indonesian nation. As scholars, kiai, and leaders of Sufi orders, they have played an essential role in growing nationalism and consistently preaching Islam, especially in efforts to strengthen the spirit of love for the motherland and nation. The peculiarity of Habib Luthfi's da'wah is a massive da'wah movement to care for and maintain the integrity of the Unitary State of the Republic of Indonesia. The da'wah method used by Habib Luthfi is gentle and does not hurt other people's feelings. Habib Luthfi received all the guests who came to his house and they were comfortable and felt sheltered by the shade of Habib Luthfi's words and views. This is the preaching of the Prophet Muhammad carried out by Habib Luthfi. The virtue of preaching Habib Luthfi is without drawing a sword or killing people. He never cursed or wished non-Muslims badly. Habib Luthfi's preaching style is charismatic, and the communication style is natural and elegant. Da'wah style and pattern of thinking out of the box from most people. The concept of Habib Luthfi's da'wah has been able to package the three pillars of community empowerment, namely religion, nationalism, and economic growth, more attractively.